A Critical Analysis of Collaborative Law as a Dispute Settlement Mechanism - Ni Wayan Desi Aryanti (Faculty of law Udayana University, 2019)
The increasing number of practitioners who employ Collaborative Law as an alternative dispute resolution method indicates its relevance in resolving legal cases, especially in the field of Family Law. Following its incorporation into legislation in some States in the United States of America, the current practice of Collaborative Law seems to run further than what was developed in 1990 by a family lawyer, Stuart Webb in Minneapolis. This article attempts to expose that while Collaborative Law is beneficial in resolving family disputes, its distinct feature-disqualification provision poses some drawbacks to disputants. Besides, it assesses how clients screening and combining Collaborative Law with mediation can minimize disqualification provision’s disadvantages. Lastly, this article examines why Collaborative Law’s application in non-family disputes is limited.